Selecting Appropriate Tests to Assess the Benefits of Bilateral Amplification With Hearing Aids - Jelmer van Schoonhoven; Michael Schulte; Monique Boymans; Kirsten C. Wagener; Wouter A. Dreschler; Birger Kollmeier (Trends in Hearing, 2016)
The aim of this study was to investigate the effect of bilateral hearing aids (HA) in subjects with mild and moderate-to-severe hearing loss. This study was designed as a within-subject feasibility study. Bilateral HA use was assessed using different laboratory tests on speech reception, listening effort, noise tolerance, and localization. All data were evaluated with bilateral and unilateral HA fittings. Forty experienced bilateral HA users were included with hearing impairment ranging from mild to moderate-to-severe. Subjects were stratified into two groups based on the degree of hearing loss. Speech reception in noise, listening effort, and localization tests showed a bilateral benefit for the moderate-to-severely hearing-impaired subjects. A bilateral benefit was also observed for listening effort in the mildly hearing-impaired group. The assessment of listening effort shows promise as a measure of bilateral HA benefit for mild hearing impairment. Localization and speech reception in noise tests provide additional value for larger losses. The next step is to compare experienced unilateral with bilateral HA users.